IMPLEMENTASI PELAYANAN BRIMOB TERHADAP MASYARAKAT - Leksono, Bambang Budi (MAGISTRA Law Review, 2024)
This article discusses the concept, principle, and basic principles of public service based on e-government, as well as the implementation of public service based on e-government by Brimob Polri as a public service unit that is responsible for security and public order. This article uses a normative legal research method with a specific approach, namely content analysis, comparative analysis, and normative analysis. The data used in this study are secondary data, namely primary legal data, secondary legal data, and tertiary legal data. The results of the study show that Brimob Polri has made various efforts to reform and innovate in order to improve the quality, effectiveness, and efficiency of public service based on e-government, but there are still some problems that hinder the implementation process of public service. This article provides recommendations and suggestions for improving and enhancing public service based on e-government by Brimob Polri, as well as contributing to the development of science, especially legal science, and benefits for the government, especially Brimob Polri, and the community.